Validation of Stainless-Steel CHS Columns Finite Element Models - Jindra, Daniel; Kala, Zdeněk; Kala, Jiří (MDPI, 2021)
Stainless-steel elements are increasingly used in a wide range of load-bearing structures due to their strength, minimal maintenance requirements, and aesthetic appearance. Their response differs from standard steels; therefore, it is necessary to choose a different procedure when creating a correct computational model. Seven groups of numerical models differing in the used formulation of elements integration, mesh density localization, nonlinear material model, and initial geometric imperfection were calibrated. The results of these advanced simulations were validated with published results obtained by an extensive experimental approach on circular hollow sections columns. With regard to the different slenderness of the cross-sections, the influence of the initial imperfection in the form of global and local loss of stability on the response was studied. Responses of all models were validated by comparing the averaged normalized ultimate loads and the averaged normalized deflections with experimentally obtained results.

Stainless-steel elements are increasingly used in a wide range of load-bearing structures due to their strength, minimal maintenance requirements, and aesthetic appearance. Their response differs from standard steels; therefore, it is necessary to choose a different procedure when creating a correct computational model. Seven groups of numerical models differing in the used formulation of elements integration, mesh density localization, nonlinear material model, and initial geometric imperfection were calibrated. The results of these advanced simulations were validated with published results obtained by an extensive experimental approach on circular hollow sections columns. With regard to the different slenderness of the cross-sections, the influence of the initial imperfection in the form of global and local loss of stability on the response was studied. Responses of all models were validated by comparing the averaged normalized ultimate loads and the averaged normalized deflections with experimentally obtained results.
Validation of Stainless-Steel CHS Columns Finite Element Models
Keywords: stainless steel; finite element numerical model; numerical model validation; Ramberg and Osgood model; CHS column buckling; stainless steel; finite element numerical model; numerical model validation; Ramberg and Osgood model; CHS column buckling